Efektivitas Learning Cycle 7E Terhadap Hasil Belajar Biologi pada Materi Sistem Organisasi Kehidupan Makhluk Hidup - Rohmadi, Mukhlis; Septiana, Nurul (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – This research is based on the problem of the completeness of learning of grade VII students of SMPN 8 Palangka Raya on the material of the organization system of living, which is caused by the limited facilities so that it causes low interest and activeness of students during learning. This study was conducted to test the effectiveness of the application of the Learning Cycle 7E model to biology learning outcomes.Method – The research design used was an unequal control group. The sample in this study was grade VII students of SMP N 8 Palangka Raya who were selected by purposive sampling. The number of participants will be adjusted according to class availability and approval from the school. Data analysis uses a t-test calculated using the SPSS application for Windows Version 21.0. Findings – The results of the Paired Sample t-test on the learning outcome score of the students of the experimental group, which resulted in an Asymp. Sig. (2-tailed) value of 0.000. Based on the decision criteria (Asymp. Sig. (2-tailed) < 0.05), H0 was rejected, and Ha was accepted. Therefore, it can be concluded that the learning model of the 7E Learning Cycle has a significant influence on student learning outcomes. Research Implications – The findings suggest educators to integrate the 7E Learning Cycle as a key strategy in the teaching of abstract science material. The theoretical contributions of the 7E Learning Cycle model support the view that active learning is key, and that knowledge is built by students based on existing experiences and ideas. Practical recommendations from this study are implementation steps that teachers can apply to maximize the effectiveness of learning models, encourage constructivist learning, and use comprehensive formative assessments.